Hubungan Intensitas Kebisingan terhadap Peningkatan Tekanan Darah Pekerja di Bagian Proses Grinda dan Permesinan Ceper, Klaten Jawa Tengah - WIDIANI, HAFIFAH, dr. Hardjanto MS.Sp.OK, Tanjung Anitasari IK, SKM, M.Kes (2016)
PT. Baja Kurnia is a metal casting industry that produces refined metals such as clutch, ornaments of metal or lamppost. The production process in PT. Baja Kurnia used machines like grinding, lathes and other tools that make noise. Machines that generate noise above the NAB may expose workers and increase the risk of occupational disease in workers such as increased blood pressure. The purpose of this study was to determine the relationship of the intensity of the noise contained in the tool grinding and machining to elevated blood pressure of workers at PT. Baja Kurnia Ceper, Klaten. This study was an observational study with cross sectional design. The population in this study were 65 workers with 25 workers division at the grindstone and 40 workers parts of the machinery and the sampling technique by means exhautive sampling or taking the entire population. The results of this study showed that the intensity of noise at the grinding of 100 dB and the machining section is equal to 85 dB. Based on Chi-Square test results showed there was the relationship between the intensity of noise with raised blood pressure (p = 0.019; PR 1,94 with 95% CI = 1.364 to 11.416) Keywords: Industrial metal casting, the intensity of noise, increased blood pressure